2005
DOI: 10.1016/j.numecd.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year prospective randomized controlled clinical trial of group care in type 1 diabetes

Abstract: Summary Background and aims: We showed that continuing education can be embedded into routine diabetes care by seeing patients in small groups rather than individually. Group care was cost-effective in improving quality of life, knowledge of diabetes, health behaviours and clinical outcomes in people with type 2 diabetes. The aim of this study was to verify if group care can also be applied to type 1 diabetes. Methods and results: Randomized, controlled clinical trial comparing 31 patients managed by group car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 33 publications
0
71
1
Order By: Relevance
“…Previous research has provided insight into why group classes may result in better care and outcomes than individual counselling: group classes tend to be longer in duration than individual visits, and the information received from group classes is rated as more "useful" by patients than that received at individual counselling; patients also value being able to share problems with similarly affected people. 12 Given that group classes are a more efficient use of self-management education resources (since providers can deliver care to multiple patients simultaneously), the finding that they also reduce acute complications and improve quality of care suggests that they should be the preferred method of delivering self-management education support where it is feasible to do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has provided insight into why group classes may result in better care and outcomes than individual counselling: group classes tend to be longer in duration than individual visits, and the information received from group classes is rated as more "useful" by patients than that received at individual counselling; patients also value being able to share problems with similarly affected people. 12 Given that group classes are a more efficient use of self-management education resources (since providers can deliver care to multiple patients simultaneously), the finding that they also reduce acute complications and improve quality of care suggests that they should be the preferred method of delivering self-management education support where it is feasible to do so.…”
Section: Discussionmentioning
confidence: 99%
“…11 In a pair of trials, investigators from Italy examined 62 patients with type 1 diabetes for three years and 112 with type 2 diabetes for five years after random assignment to regular group classes versus individual visits. 12,13 Those allocated to group classes demonstrated better diabetes knowledge and health behaviours, and had better quality of life. In the type 2 diabetes trial, they also had greater reductions in body weight and HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…There is however scope for further improvement, by implementing new approaches to care which involve a major redefinition of the roles and relationships between health care professionals and patients (2). In a previous study, we measured similar DQOL scores in adult patients with T1DM followed by usual care and an improvement after 3 years of an approach which substituted traditional top-down one-to-one visits with interactive group education sessions (26). Further addition of a structured carbohydrate counting programme improved not only QoL but also HbA1c and coping skills (27).…”
Section: Discussionmentioning
confidence: 99%
“…We then decided to produce a brief summary of the quality of the four key reviews 18,83,85,87 in order to assess any uncertainties underpinning their results (Table 11).…”
Section: Review Qualitymentioning
confidence: 99%
“…many-to-many interaction) was reported in 14 studies. 63,64,66,68,70,71,[73][74][75][76][77]82,85,86 Eleven studies explicitly reported health education/information presentation(s) by individual clinicians, 57,60,65,[66][67][68]70,71,[73][74][75]79 with one for health education/information presentation(s) by multiple clinicians 63 and two for health education/information via booklet, leaflet or video. 70,80 Seven studies reported medication review and four describe completion of prescriptions.…”
Section: Intervention Componentsmentioning
confidence: 99%